2013
DOI: 10.4103/2278-9626.112318
|View full text |Cite
|
Sign up to set email alerts
|

Effect of maternal periodontal status on birth weight

Abstract: Aim: The study was to determine the effect of maternal periodontal status on birth weight. Materials and Methods: This longitudinal study was conducted at the University of Benin Teaching Hospital, Benin City, Edo State. Recruited into the study were 300 pregnant women aged between 20 and 34 years who were randomly placed into two groups. Test group received oral prophylaxis upon enrolment and control group received prophylaxis after deliveries. The gestational age for enrolment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(26 citation statements)
references
References 33 publications
0
26
0
Order By: Relevance
“…Improving the oral health of pregnant women prevents complications of dental diseases during pregnancy [ 6 ]. Maternal oral diseases have been associated with pre-term births [ 7 - 10 ], development of pre-eclampsia [ 11 , 12 ] and delivery of a “small-for-gestational-age” infant [ 7 , 9 , 10 ]. This could lead to infant mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the oral health of pregnant women prevents complications of dental diseases during pregnancy [ 6 ]. Maternal oral diseases have been associated with pre-term births [ 7 - 10 ], development of pre-eclampsia [ 11 , 12 ] and delivery of a “small-for-gestational-age” infant [ 7 , 9 , 10 ]. This could lead to infant mortality and morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The respondents in this study were doctors undergoing postgraduate medical training in a tertiary health institution compared to the Jordanian study where the respondents were doctors working in maternities, comprehensive health centers and other hospitals. Studies have suggested that treatment of periodontal disease in pregnancy is feasible and may reduce the risk of preterm birth [6,7]. Only one-third of the sample agreed with this statement.…”
Section: Discussionmentioning
confidence: 80%
“…Umoh et al, [6] in a Nigerian study to investigate the effect of maternal periodontal status on birth weight, reported low birth weight deliveries which were significantly associated with poor periodontal status and concluded that periodontal treatment was effective in preventing low birth weight deliveries. It has been reported that controlling plaque by brushing, flossing and professional prophylaxis, including scaling and root planing, help to achieve good oral health in pregnancy and prevent low birth weight [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lopez and colleagues also assessed the risk of preterm birth and low birth weight in women with periodontitis in the USA and found that pregnant women with periodontitis were at a high risk of giving birth to premature babies with low birth weight (p=0.0004; RR=3.5) 36 .Several other studies also con rmed the association 37 , 38 , 39 , 40 , 41 , 42 , 14 , 43 . Also in Africa, some studies have been done on preterm birth and low birth weight deliveries and these were signi cantly associated with poor periodontal status; for example a study done in Nigeria by Umoh and colleagues revealed that periodontal treatment was effective in preventing low birth weight deliveries 20 . In Uganda, Wandera and colleagues also found that mothers with periodontal problems and poor oral hygiene during pregnancy had a greater risk of preterm birth as opposed to mothers who did not have periodontitis during pregnancy 44 and Muwazi in Uganda in his cross-sectional study revealed the association between gingival recession and preterm birth 31 .…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, some studies have associated poor periodontal status with premature birth and low birth weight deliveries. For example, a study done in Nigeria by Umoh and colleagues concluded that the management of periodontal diseases reduced the prevalence of low birth weight deliveries 20 . Although the studies highlighted the association between periodontal infection and the risk of low birth weight, the literature search conducted did not nd any study that pointed to periodontal screening during pregnancy.…”
Section: Introductionmentioning
confidence: 99%